Standardization of Homoeopathic Drug Ruta graveolens L. - Y.D. Niturkar, D. A. Dhale, S. K. Markandeya and (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Ruta graveolens<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> L. is a small, strong scented perennial herb belonging to family Rutaceae. It is having a broad sphere of action & hence a potential drug in homoeopathy. It has antihysteric, emmenagogic, ophthalmic, vermifuge, carminative, antiepileptic, revulsive, anthelmentic, abortive, spasmolytic properties. It has both curative and injurious on the fibrous and bony tissues, especially in the vicinity of joints. In the present paper, the pharmacognostic and physio-chemical investigations on the leaves and stem of the plant have been presented. Morphological and anatomical characters of leaf and stem are studied in detailed. Physio-chemical parameters of raw drug viz., moisture content, ash values, extractives values, as well as quantitative estimation of various phytochemicals have been studied.